Vloga organizacijske kulture in klime pri fluktuaciji zaposlenih v gostinstvu - Krajnc, Evelin (Mednarodno inovativno poslovanje, 2023)
Hospitality is extremely labour intensive industry, with employee turnover higher than in other industries, and substantial human resource issues. Structural changes due to Covid-19 restrictions increased employee negative turnover rate and further increased labour related issues of hospitality industry. High employee turnover has decadeslong history and it appears that industry and policy makers failed to find and implement effective solutions. In the context of Slovenian hospitality industry, we empirically examine to role of perceived organizational culture and climate in potential employee negative turnover. Using quantitative methodology we investigate perceived organizational culture and climate among 219 employees at different positions, with different working experiences. Findings show moderate organizational culture and climate, and moderate potential employee negative turnover. Around 50% of respondents report high likelihood of leaving current employer or changing professional career. Highly rated dimensions of culture and climate pertain to activities oriented to guests and productivity. Low rated dimensions pertain to processes oriented to employees and their wellbeing.
Keywords: employee turnover; fluktuacija kadrov; Gostinci; gostinska dejavnost; hospitality industry; Organizacijska klima; organizacijska kultura; organizational climate; organizational culture